Analisis Kesalahan Siswa Menyelesaikan Soal Cerita Persamaan Linear Satu Variabel Kelas VIII SMP Negeri 5 Palu Berdasarkan Teori Newman - Dwi Permatasari; Gandung Sugita; Mustamin Idris; Anggraini Anggraini (Aksioma, 2026)
This study aims to analyse the errors made by students in solving Linear Equation One Variable (PLSV) story problems in class VIII students of SMP Negeri 5 Palu, using Newman's theory. Newman's theory consists of five stages which include reading errors, understanding errors, transformation errors, process skill errors, and errors in writing the final answer or notation. This research used qualitative method with descriptive approach. The data collection techniques were through written tests and interviews. The research subjects consisted of three students based on the level of mathematical ability, namely high mathematical ability, medium mathematical ability, and low mathematical ability seen from the report card scores of mathematics subjects in class VII even semester. The results showed that students with high mathematics ability made reading errors, transformation errors, process skill errors, and errors in writing the final answer or notation. The students with medium mathematics ability made reading errors, comprehension errors, transformation errors, process skill errors, and errors in writing the final answer or notation. Similarly, students with low mathematics ability made reading errors, comprehension errors, transformation errors, process skills errors, and errors in writing the final answer or notation. Errors that often occur at the reading error stage are misreading the symbols in the problem, transformation errors, namely changing the problem into mathematical form, process skill errors, namely errors in counting operations, and errors in writing the final answer or notation.